Age-related differences in default-mode network connectivity in response to intermittent theta-burst stimulation and its relationships with maintained cognition and brain integrity in healthy aging - Abellaneda-Pérez, Kilian; Vaqué-Alcázar, Lídia; Vidal-Piñeiro, Dídac; Jannati, Ali; Solana, Elisabeth; Bargalló, Núria; Santarnecchi, Emiliano; Pascual-Leone, Alvaro; Bartrés-Faz, David (NeuroImage (Orlando, Fla.), 2019)
The default-mode network (DMN) is affected by advancing age, where particularly long-range connectivity has been consistently reported to be reduced as compared to young individuals. We examined whether there were any differences in the effects of intermittent theta-burst stimulation (iTBS) in DMN connectivity between younger and older adults, its associations with cognition and brain integrity, as well as with long-term cognitive status. Twenty-four younger and 27 cognitively normal older adults were randomly assigned to receive real or sham iTBS over the left inferior parietal lobule between two resting-state functional magnetic resonance imaging (rs-fMRI) acquisitions. Three years later, those older adults who had received real iTBS underwent a cognitive follow-up assessment. Among the younger adults, functional connectivity increased following iTBS in distal DMN areas from the stimulation site. In contrast, older adults exhibited increases in connectivity following iTBS in proximal DMN regions. Moreover, older adults with functional responses to iTBS resembling those of the younger participants exhibited greater brain integrity and higher cognitive performance at baseline and at the 3-year follow-up, along with less cognitive decline. Finally, we observed that ‘young-like’ functional responses to iTBS were also related to the educational background attained amongst older adults. The present study reveals that functional responses of the DMN to iTBS are modulated by age. Furthermore, combining iTBS and rs-fMRI in older adults may allow characterizing distinctive cognitive profiles in aging and its progression, probably reflecting network plasticity systems that may entail a neurobiological substrate of cognitive reserve. •iTBS exerts distinctive effects in DMN connectivity in younger and older adults.•iTBS-fMRI metrics can identify meaningful associations between brain networks functioning and cognition in aging.•The iTBS-fMRI approach can allow to distinguish different cognitive trajectories in aging.•iTBS-fMRI measures could reflect a network plasticity mechanism of cognitive reserve.